Robert S. Anderson y Walter Huber, The Hour of the Fox. Tropical Forests, the World Bank, and Indigenous Peoples in Central India. Seattle y Londres: University of Washington Press, 1988. 158 pp. Mapas y fotografías. - Devalle, Susana B. C. (Estudios de Asia y África, 1989)
-